PENDIDIKAN ANTI KORUPSI SEBAGAI PENDIDIKAN AKHLAK DALAM PENDIDIKAN AGAMA ISLAM - Budiman, Amat (Jurnal Pendidikan Guru, 2017)
Abominable human morals which marked one of them with acts of corruption continue to be entrenched, there is even a fear that this culture regenerates attack children. This article is aimed confirm the presence of anti-corruption education as a part of moral education in the perspective of Islamic religious education. The essence of corruption is the misuse of authority with the aim of benefit and enrich themselves to the detriment of others. Corruption is identical with, or ineffective or irresponsible, ungrateful for the gift of God and kept up-to feel deprived, not sociable because of corruption harm others, and dishonest. For prevention, one of the strategic action is to make a move together through anti-corruption education. Anti-corruption education as a part of moral education in the perspective of Islamic religious education is derived from the Quran are expected to instill and develop virtues in the young generation, as trustee or responsible, grateful for the gift of God Almighty, and honest as forms of devotion to Allah (subject to the order of Allah).